Enlightenment of Growth Plate Regeneration Based on Cartilage Repair Theory: A Review - Wang, Xianggang; Li, Zuhao; Wang, Chenyu; Bai, Haotian; Wang, Zhonghan; Liu, Yuzhe; Bao, Yirui; Ren, Ming; Liu, He; Wang, Jincheng (Frontiers in Bioengineering and Biotechnology, 2021)
The growth plate (GP) is a cartilaginous region situated between the epiphysis and metaphysis at the end of the immature long bone, which is susceptible to mechanical damage because of its vulnerable structure. Due to the limited regeneration ability of the GP and current clinical treatment strategies (e.g., bone bridge resection and fat engraftment) always result in bone bridge formation, which will cause length discrepancy and angular deformity, thus making satisfactory outcomes difficult to achieve. The introduction of cartilage repair theory and cartilage tissue engineering technology may encourage novel therapeutic approaches for GP repair using tissue engineered GPs, including biocompatible scaffolds incorporated with appropriate seed cells and growth factors. In this review, we summarize the physiological structure of GPs, the pathological process, and repair phases of GP injuries, placing greater emphasis on advanced tissue engineering strategies for GP repair. Furthermore, we also propose that three-dimensional printing technology will play a significant role in this field in the future given its advantage of bionic replication of complex structures. We predict that tissue engineering strategies will offer a significant alternative to the management of GP injuries.